1983
DOI: 10.2307/3429747
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Biological Studies of Coal and Oil Fly Ash

Abstract: Studies were performed to compare the physical and chemical characteristics and the in vitro macrophage cytotoxicity of oil and coal fly ash. Sampling methodology was developed to collect size-fractionated particulate matter from the smokestack of either a coal-fired or an oil-fired power plant. Morphological studies demonstrated particle heterogeneity, although most coal fly ash particles appeared to be spherical. Oil fly ash contained two major morphologies; nonopaque amorphous particles and opaque amorphous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
0
11
1
Order By: Relevance
“…Glass beads have been reported to cause only minimal reactions in the lung (Fisher et al, 1983), and essentially no reaction was observed in this study. In contrast, a fibrotic response has been produced by instillation or inhalation of quartz in experimental animals (Martin et al, 1983;Reiser et al, 1983;Adamson & Bowden, 1984;Callis et al, 1985).…”
Section: Discussioncontrasting
confidence: 58%
“…Glass beads have been reported to cause only minimal reactions in the lung (Fisher et al, 1983), and essentially no reaction was observed in this study. In contrast, a fibrotic response has been produced by instillation or inhalation of quartz in experimental animals (Martin et al, 1983;Reiser et al, 1983;Adamson & Bowden, 1984;Callis et al, 1985).…”
Section: Discussioncontrasting
confidence: 58%
“…Particulate matter from the combustion of residual oil is composed of a high content of water-soluble sulfate and metals, including vanadium, nickel, and iron, in comparison to other forms of particulate matter (Fisher et al, 1983;Hatch et al, 1985). Several recent animal studies have suggested that metal components of residual oil fly ash (ROFA) may be major determinants of its pulmonary toxicity (Pritchard et al, 1996;Kodavanti et al, 1997;Dreher et al, 1997).…”
Section: Introductionmentioning
confidence: 96%
“…Fly ash from fossil and waste fuel combustion contributes more than 2.5 × 10 5 tons annually to the ambient air PM burden in the United States (3). Although the ash content of oil used for electric power generation is two to three orders of magnitude less than that of coal, many oil-fired power plants employ few or no particle emission abatement technologies (4). Consequently, fugitive fly ash from the combustion of oil and residual fuel oil contributed 76,000 and 49,000 tons, respectively, to the national ambient particle burden in 1992 (5).…”
mentioning
confidence: 99%